2005
DOI: 10.1021/jp047395j
|View full text |Cite
|
Sign up to set email alerts
|

Using MD Snapshots in ab Initio and DFT Calculations:  OH Vibrations in the First Hydration Shell around Li+(aq)

Abstract: The average OH stretching vibrational frequency for the water molecules in the first hydration shell around a Li(+) ion in a dilute aqueous solution was calculated by a hybrid molecular dynamics + quantum-mechanical ("MD + QM") approach. Using geometry configurations from a series of snapshots from an MD simulation, the anharmonic, uncoupled OH stretching frequencies were calculated for 100 first-shell OH oscillators at the B3LYP and HF/6-31G(d,p) levels of theory, explicitly including the first shell and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 49 publications
3
53
1
Order By: Relevance
“…20,[37][38][39] Explicit polarizability may be important for understanding this, but in this case it is the polarization of the solvent molecules at short separations from the small Li + ion that is crucial. 40,41 The sensitivity of the Li + -water solvation structure can also be inferred from the analysis of extensive experimental studies, which have raised questions about the relative stability of water around Li + . 39,[42][43][44] In particular, it is still unclear whether the Li + -water coordination number is closer to 4 or 6 at moderate concentrations, ∼ 1 M.…”
Section: -36mentioning
confidence: 99%
“…20,[37][38][39] Explicit polarizability may be important for understanding this, but in this case it is the polarization of the solvent molecules at short separations from the small Li + ion that is crucial. 40,41 The sensitivity of the Li + -water solvation structure can also be inferred from the analysis of extensive experimental studies, which have raised questions about the relative stability of water around Li + . 39,[42][43][44] In particular, it is still unclear whether the Li + -water coordination number is closer to 4 or 6 at moderate concentrations, ∼ 1 M.…”
Section: -36mentioning
confidence: 99%
“…Further, there are several simulation studies, which have been able to identify residence times in anionic solvation shells, rotational anisotropy apart from ion‐solvent structures . Yet, only a few of them have focused on theoretical calculations of vibrational lineshape and spectral diffusion timescales . Skinner and coworkers employed an approach where an empirical relationship between instantaneous vibrational frequency was developed and subsequently used to calculate the electric field applied along the vibrational mode of interest and thus obtaining vibrational lineshapes and vibrational spectral diffusion timescales .…”
Section: Introductionmentioning
confidence: 99%
“…[16,[34][35][36] Yet, only a few of them have focused on theoretical calculations of vibrational lineshape and spectral diffusion timescales. [37][38][39][40] Skinner and coworkers employed an approach where an empirical relationship between instantaneous vibrational frequency was developed and subsequently used to calculate the electric field applied along the vibrational mode of interest and thus obtaining vibrational lineshapes and vibrational spectral diffusion timescales. [4,[20][21][22]38] In another classical simulation study, the solvation shell dynamics around anion was investigated using theoretically simulated pump-probe spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…13, Wheeler et al have suggested principal mode analysis (PMA) 11,27 in which the average massweighted normal modes and associated frequencies are calculated from a classical MD trajectory by evaluating the eigenvectors and eigenvalues of the covariance matrix associated with the mass-weighted displacements of the molecular coordinates from their equilibrium positions. [49][50][51] The instantaneous normal mode analysis (INMA) and its variants [31][32][33][34][35][36] are obtained by diagonalizing the Hessian matrix at each instantaneous configuration of the molecule. when the potential energy surface of the molecule is anharmonic or when the thermal equilibrium is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%